(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
In this work is analysed an Iberian inscription of three signs, lube, found at the site San Miguel III of Castejón de Monegros at the external face of a black glaze ‘Campanian’ dish. The inscription is complete and probably indicates the name of the owner of the dish. The personal name lube does not fit as an Iberian personal name, but it could be the Iberised form of the Celtiberian personal name lubos, which is documented frequently in the Botorrita bronze plates.